Pension Reforms, Longer Working Horizons and Depression. Does the Risk of Automation Matter? - Marco Bertoni; Giorgio Brunello; Filippo Da Re (Institute of Labor Economics (IZA), 2022)
We investigate the effect of postponing minimum retirement age on middle-aged workers' depression. Using pension reforms in several European countries and data from the SHARE survey, we find that depression increases with a longer work horizon, but only among workers employed in occupations with a relatively high risk of automation. We rule out alternatives to this risk, including job strenuousness, education, gender, and the degree of routinization of occupations. We explain our results with the higher job insecurity associated with occupations more exposed to automation.
Keywords: I1; J24; J26; O33; 330; pension reforms; depression; automation; SHARE